EXPLORATION OF WOMEN'S EMPLOYMENT IN SCIENTIFIC RESEARCH IN UZBEKISTAN - Irmatova Aziza Bakhramovna (Research Parks Publishers, 2020)
The paper presents an econometric analysis of female employment in Uzbekistan's research sphere and socio-economic factors affecting it, as well as draws relevant conclusions and recommendations for increasing female employment in this sphere